2010
DOI: 10.1177/003172171009100807
|View full text |Cite
|
Sign up to set email alerts
|

The Delicate Task of Developing an Attractive Merit Pay Plan for Teachers

Abstract: We've spent four years assessing claims about the potential for implementing performance-based pay (or merit pay) for educators in elementary and secondary schools. In the theoretical realm, passionate promoters of merit pay have argued that such a scheme would properly align incentives for teachers so the most talented are recruited, the best are rewarded, and the laggards are relocated to a different profession. On the other hand, fervent foes of the practice contend that performance pay would not capture al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some reasons for opposition might include the fears that these schemes facilitate a narrowing of the curriculum (Wilms and Chapleau 1999); are often based on unreliable assessments (Koedel 2009); potentially reduce the incentives to collaborate (Ritter and Jensen 2010); and could negatively impact teachers' intrinsic motivations (Ryan, Connell, and Deci 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Some reasons for opposition might include the fears that these schemes facilitate a narrowing of the curriculum (Wilms and Chapleau 1999); are often based on unreliable assessments (Koedel 2009); potentially reduce the incentives to collaborate (Ritter and Jensen 2010); and could negatively impact teachers' intrinsic motivations (Ryan, Connell, and Deci 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers might worry more about the reliability of tests and their abilities to accurately assess student performance (Ballou & Springer, 2015;Hart, 2015;Koedel, Mihaly, & Rockoff, 2015;Lavigne, 2014). They also could have concerns about the designs of performance incentives and how they may affect a school's environment, such as inducing competition that reduces efforts to collaborate (Goldhaber, DeArmond, Player, & Choi, 2008;Ritter & Jensen, 2010) or enticing teachers to cheat (Jacob & Levitt, 2003). Another consideration is that introducing rewards that are tied to assessments might cause teachers to feel a loss of autonomy in the classroom (Popkewitz & Lind, 1989) and to more narrowly focus on objectives tied to test scores at the expense of outcomes that fit into a broader mission or understanding of the roles of education (Murnane & Cohen, 1986;Wilms & Chapleau, 1999).…”
Section: Teacher Pay In the United Statesmentioning
confidence: 99%
“…The focus on a single sector is reasonable, considering a finding by the OECD (2005) that the prevalence of performance-based pay depends on the area of public service. In education, a properly designed merit-based pay is seen as a means of aligning teachers’ incentives to act with a school’s mission (Ritter & Jensen, 2010; Ritter et al, 2009). Studies have found a positive impact of performance-based pay on students’ test scores in India (Muralidharan & Sundararaman, 2011) and the United States (Cooper & Cohn, 1997), although Dee and Keys (2004) found that a merit-based system in the US state of Tennessee had “mixed success” with rewarding good teachers (p. 471).…”
Section: Introductionmentioning
confidence: 99%